Membangun Karakter Sehat dan Berakhlak Mulia melalui 7 Kebiasaan Anak Indonesia Hebat - Neng Nurcahyati Sinulingga (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
Character education is a crucial element in building a healthy, smart, and noble golden generation of Indonesia towards the vision of Indonesia 2045. This article aims to analyze the concept of building children's character through the implementation of the 7 Habits of Great Indonesian Children Movement, which includes the habits of waking up early, worshiping, exercising, eating healthy and nutritious, enjoying learning, socializing, and sleeping early. This research uses a literature study approach by analyzing literature from academic journals, books, scientific articles, and research reports. The data was analyzed interpretively to identify the relevance of the implementation of these habits in the character building of Indonesian children. The results showed that these positive habits not only support children's physical and mental development, but also instill moral values, discipline, responsibility and empathy, which are relevant to Islamic teachings and global needs. The program reflects a holistic approach to character education based on spiritual, social and health values, supported by synergy between family, school and community. However, challenges in implementation include the influence of technology, limited facilities and a lack of community understanding of the importance of habit-based character education. Strategies such as integrating character education in the curriculum, involving parents and communities, and utilizing technology wisely are key to the success of this movement.